Penilaian Keamanan Aplikasi Berbagi Berkas Aufratia Menggunakan Standar Iso 27001 - Khurin In Noviarani; Walied Ghaly; Johan Ferliansyah (Jurnal Mahasiswa Manajemen, 2020)
Abstract Background - The Covid-19 pandemic has an impact on the educational aspect of using online internet media. however, storage media for online activities is still lacking. Especially the lack of flexibility, space for modification and privacy controls provided free of charge by existing file sharing service providers provide various obstacles in accelerating and exchanging information and data using file sharing media services, this is what makes various universities and their academics to develop their file sharing services. Purpose - to evaluate the results of the quality of information security from the Aufratia file sharing application developed independently by the UMG academic community. Design / methodology / approach - This research is a descriptive qualitative research type, while the root cause analysis uses the Fishbone Diagram. Findings - The Aufratia application still does not meet the ISO 27001 standard. Information protection is minimal and almost non-existent, making Aufratia unfit to be a release application and currently it is more suitable to be a beta version (tested) application. Research implications - This research provides a contribution in terms of developing file sharing application software that utilizes the internet. Research limitation - Research only examines one software, further research can be modified or compared with other software to assess the advantages and disadvantages that can be used to complement each other.